MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN MUTU PEMBELAJARAN - Enong Rohayati; Ulfah Wahyu Harzegovina; Yayah Sofiah; Rohmawiani Rosalina (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the management of educational facilities and infrastructure at SD Pandeglang 14 and its contribution to improving learning quality. The research focuses on planning, procurement, utilization, maintenance, inventory management, and supervision of school facilities and infrastructure. A descriptive qualitative approach was employed involving the principal, teachers, and administrative staff as research participants. Data were collected through interviews, observations, and documentation studies. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of educational facility management practices. The findings reveal that facilities and infrastructure management at SD Pandeglang 14 has been implemented systematically through needs-based planning, priority-oriented procurement, regular maintenance, and well-organized inventory administration. The availability of adequate classrooms, learning media, library resources, and sanitation facilities positively supports the effectiveness of the learning process. However, challenges remain, particularly related to budget limitations and the need for technology-based facility development. The study concludes that effective management of educational facilities and infrastructure contributes significantly to creating a conducive learning environment and enhancing the quality of learning in primary schools.